Infamous Bodies Early Black Women's Celebrity and the Afterlives of Rights - Pinto, Samantha (Duke University Press, 2020)
The countless retellings and reimaginings of the private and public lives of Phillis Wheatley, Sally Hemings, Sarah Baartman, Mary Seacole, and Sarah Forbes Bonetta have transformed them into difficult cultural and black feminist icons. In Infamous Bodies, Samantha Pinto explores how histories of these black women and their ongoing fame generate new ways of imagining black feminist futures. Drawing on a variety of media, cultural, legal, and critical sources, Pinto shows how the narratives surrounding these eighteenth- and nineteenth-century celebrities shape key political concepts such as freedom, consent, contract, citizenship, and sovereignty. Whether analyzing Wheatley's fame in relation to conceptions of race and freedom, notions of consent in Hemings's relationship with Thomas Jefferson, or Baartman's ability to enter into legal contracts, Pinto reveals the centrality of race, gender, and sexuality in the formation of political rights. In so doing, she contends that feminist theories of black women's vulnerable embodiment can be the starting point for future progressive political projects.